2018
DOI: 10.1002/aocs.12094
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance and Seed Inorganic Phosphorus Stability of Low‐Phytate Soybean Line TN09‐239

Abstract: Phytate (myoinositol‐1,2,3,4,5,6‐hexa‐kisphosphate) in soybean (Glycine max (L.) Merr.) cannot be absorbed by livestock with monogastric digestive systems, and is often excreted in their waste. This can result in agricultural runoff pollution, as well as nutritional deficiencies in poultry (Gallus Gallus domesticus) and swine (Sus domesticus). The enzyme phytase is often applied to break the phytin‐salt bonds and allow for phosphorus (P) absorption, but is an added cost for animal producers. Therefore, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It has been reported that many low-phytate mutants impact plant growth and productivity and have decreased yield as compared with sibling normal-phytate/wild-type lines [27,28,29]. However in the case of soybean lines developed from crosses using the same low-phytate parent used here, CX1834 [14], previous studies demonstrated that while yields of low-phytate progeny were 85% to 90% of sibling normal-phytate lines, the yield loss was largely due to negative impacts on germination and emergence that led to reduced stand establishment, rather than impacts on plant growth and productivity subsequent to emergence and germination [30,31]. Therefore, in this study, we further investigated whether in the low-phytate lines that we bred, there was an effect on the growth, photosynthesis, nitrogen fixation, seed yield, and seed quality subsequent to germination and emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that many low-phytate mutants impact plant growth and productivity and have decreased yield as compared with sibling normal-phytate/wild-type lines [27,28,29]. However in the case of soybean lines developed from crosses using the same low-phytate parent used here, CX1834 [14], previous studies demonstrated that while yields of low-phytate progeny were 85% to 90% of sibling normal-phytate lines, the yield loss was largely due to negative impacts on germination and emergence that led to reduced stand establishment, rather than impacts on plant growth and productivity subsequent to emergence and germination [30,31]. Therefore, in this study, we further investigated whether in the low-phytate lines that we bred, there was an effect on the growth, photosynthesis, nitrogen fixation, seed yield, and seed quality subsequent to germination and emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Tanbakuro used to breed the of the low-phytate line studied here, a similar buffering effect was obtained, either provided by variant alleles of one of the two MRP orthologs, or perhaps by other components of the Tanbakuro genome. However the most likely explanation for the good growth and performance of the low-phytate soybean lines studied here is that problems with performance of this specific genotype are probably due to negative impacts on germination and emergence, rather than to negative impacts on subsequent growth and performance [29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These issues have hindered full commercialization of this valuable trait. Nonetheless, several germplasm releases have occurred (Boehm, Walker, Bhandari, Kopsell, & Pantalone, 2017; Lee et al., 2019; Wiggins et al., 2018), with acceptable germination rates being reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, lpa mutant crops often exhibit inferior agronomic traits, e.g., low germination rate, decreased field emergence, and reduced grain weight. Therefore, cross and selection breeding of lpa mutants with commercial cultivars has been applied to improve the agronomic performance of lpa mutants. …”
Section: Introductionmentioning
confidence: 99%